2006
DOI: 10.1007/s00264-006-0253-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior debridement and bone grafting of spinal tuberculosis with one-stage instrumentation anteriorly or posteriorly

Abstract: Between 2000 and 2004, 40 cases (average age 38, range 16-65 years) of spinal tuberculosis were treated with anterior debridement and iliac bone graft with one-stage anterior or posterior instrumentation in our unit. All patients received at least 2 weeks of regular antituberculous chemotherapy before surgery. We followed up all patients for 12-48 months (mean 22 months). Local symptoms of all patients were relieved significantly 1-3 weeks postoperatively; 23 of 25 cases (92%) with neurogical deficit had excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…However, the majority of surgeons favour the anterior approach because of concern over the safety of the posterior approach [8,9]. The anterior surgical approach includes an anterolateral extrapleural approach and a transpleural anterior approach, which was developed by Hodgson et al [1,14] and has been used by many surgeons for spinal tuberculous lesions [2,[15][16][17]. The anterior approach is considered to be very important because it can provide the surgeon with direct access to the diseased vertebral segments to perform radical surgical debridement of the infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of surgeons favour the anterior approach because of concern over the safety of the posterior approach [8,9]. The anterior surgical approach includes an anterolateral extrapleural approach and a transpleural anterior approach, which was developed by Hodgson et al [1,14] and has been used by many surgeons for spinal tuberculous lesions [2,[15][16][17]. The anterior approach is considered to be very important because it can provide the surgeon with direct access to the diseased vertebral segments to perform radical surgical debridement of the infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the report of Jin et al [2], a mean of 18°of kyphosis correction was achieved in adult patients after anterior instrumentation surgery during the follow-up period. Zhao et al [27] found kyphotic deformity was corrected by an average of about 16°using anterior instrumentation and fusion, and in the follow-up period, correction loss was 1°(6.3%). According to Karaeminogullari et al [6], the mean correction loss at final follow-up (mean five years) following anterior radical debridement and fusion or posterolateral debridement, fusion and instrumentation alone was 45-50%, whereas the corresponding finding for anterior radical debridement and fusion plus posterior instrumentation and fusion was 12%.…”
Section: Discussionmentioning
confidence: 98%
“…Various surgical approaches were adopted to reduce lower lumbar spinal TB [4,5,14]. Majority of TB lesions involve the anterior and middle column; therefore, anterior debridement and bone grafting were recommended by some surgeons [15,16]. Nevertheless, the long term effect of the anterior approach showed that the bone graft was susceptible to collapse or absorption, and kyphosis was more severe [17,18].…”
Section: Clinical Datamentioning
confidence: 99%